Teacher's satisfaction toward the virtual learning environment in Malaysia - Awang, Hapini; Mat Aji, Zahurin; Sheik Osman, Wan Rozaini (Global Academic Excellence, 2018)
The current study was carried out to measure the level of teacher’s satisfaction toward the Virtual Learning Environment (VLE) implementation in Malaysia. The population of the study consists of 97,503 teachers across the Northern Region of Peninsular Malaysia. By applying the simple random sampling procedure, 850 survey instruments were distributed to the target respondents. However, after the data screening procedure, only 643 instruments were usable for further analysis. The overall mean score of teacher’s satisfaction toward VLE is 3.83. This mean score indicated that the satisfaction of experience using VLE technology among Malaysian teachers is at the moderate level. A possible explanation of this result might be related to the degree of information, system and service quality, accommodated by the VLE system and service provider to the teachers. Hence, the further examination is required to investigate the contributing factors of teacher satisfaction toward VLE implementation in Malaysia.